Analisis Hukum Terhadap Pendaftaran dan Status Perwalian Anak Angkat yang Ditetapkan sebagai Anak Kandung di Kecamatan Kota Gajah - Miftakhul Izza; Habib Sulthon Asnawi; Iwannudin Iwannudin (Assyfa Journal of Islamic Studies, 2026)
This study analyzes the practice of recording adopted children as biological children in the civil administration system in Kota Gajah District, Central Lampung Regency, as well as the influencing factors and legal implications for guardianship, inheritance, and child's identity of origin. Using a qualitative empirical juridical (socio-legal) approach with a case study method, data were collected through in-depth interviews, limited observation, and document analysis, then verified through source triangulation. The findings show that the registration practice did not originate from formal legal procedures but from social caregiving that had been ongoing since the child was an infant, driven by the adoptive family's lack of biological children, the biological family's economic limitations, and considerations of administrative convenience. The research found discrepancies between family narratives and examined documents, as well as the absence of court decisions as a formal basis. Legal implications include potential obscuring of the child's identity of origin and emerging issues in guardianship, inheritance, lineage, and mahram aspects. This study affirms that adoption issues cannot be understood merely as administrative matters but must be read as an intersection of social practice, legal certainty, and child protection within the framework of Islamic family law and positive law.